Edukasi Wirausaha dan Pendampingan Psikologis Pasca Gempa Bumi Cianjur - Herlina Herlina; Sri Mulyeni; Sri Maria Ulfha; Siti Titta Partini; Finny Redjeki (Fakultas Teknik Universitas Cenderawasih, 2023)
Earthquake disasters often have a significant impact on society, not only physically but also pshychologically and economically. Post disaster recovery not only requires efforts tto rebuild physical infrastructure, but also needs to pay serious attention to individual psychological recovery and entrepreneurial assistance for victims. Psychological recovery for Cugenang resident is an important aspect in restoring the mental well-being of individuals and communities affected by the earthquake. Counselling and trauma therapy is carried out in the community as well as children by the service team. Entrepreneurship assistance is also an important factor in rebuilding the economic sustainability of the community after the Cianjur Cugenang earthquake. This on going assistance needs to be carried out so that the recovery process also runs well and quickly.